Presence of concurrent sarcoid-like granulomas indicates better survival in cancer patients: a retrospective cohort study. Issue 4 (26th October 2020) - Murthi, Mukunthan; Yoshioka, Keiichiro; Cho, Jeong Hee; Arias, Sixto; Danna, Elio; Zaw, Moe; Holt, Greg; Tatsumi, Koichiro; Kawasaki, Takeshi; Mirsaeidi, Mehdi
Introduction: An increased risk of sarcoidosis and sarcoid-like reactions in subjects with a history of malignancy has been suggested. We assessed the incidence and clinical characteristics of cancer patients with biopsies containing sarcoid-like granulomas on cancer metastasis and patient survival. Methods: This is a retrospective, multicentre, observational study involving endobronchial ultrasound transbronchial needle aspiration and a melanoma patient dataset at the University of Miami, USA, and a sarcoidosis patient database at Chiba University, Japan. Subjects with a confirmed diagnosis of cancer and who subsequently developed granulomas in different organs were enrolled. The study was registered at Clinicaltrials.gov (NCT03844698). Results: 133 patients met the study's criteria. The most common primary cancer sites were the skin (22.5%), breast (20.3%) and lymph node (12.8%). 24 (18%) patients developed sarcoid-like granulomas within 1 year of cancer diagnosis, 54 (40.6%) between 1 and 5 years and 49 (36.8%) after 5 years. Imaging showed possible sarcoid-like granulomas in lymph nodes in 51 cases (38.3%) and lung tissue and mediastinal lymph nodes in 73 cases (54.9%); some parenchymal reticular opacity and fibrosis was found in 5 (3.7%) and significant parenchymal fibrosis in 2 (1.5%) subjects. According to logistic regression analysis, the frequency of metastatic cancer was significantly lower in patients with sarcoid-like granulomas than in controls. Moreover, multivariate Cox proportional hazard analysis showed a significant survival advantage in those with sarcoid-like granuloma. Conclusion: Sarcoid-like granulomas are uncommon pathology findings in cancer patients. There is a significant association between the presence of granulomas and reduced metastasis and increased survival. Further study is warranted to understand the protective mechanism involved. These findings suggest that patients with underlying malignancy who develop sarcoidosis and sarcoid-like reactions have a lower risk of stage 4 metastatic disease and better survival compared to patients who do not develop such granulomatous reactions https://bit.ly/2CNhc9e